(untitled) (Scientia Agropecuaria, 2023)
The purple corn cob is an agro-industrial by-product that contains high-value bioactive compounds, which makes its use attractive for the development of extraction processes. The aim of this research was to extract the bioactive compounds from the purple corn cob by high isostatic pressure at different processing temperatures. Pressures of 0.01 MPa, 250 MPa, 450 MPa and 650 MPa for 3 minutes and at temperatures of 25 °C, 45 °C and 65 °C were used. High pressure extraction was compared with conventional extraction (2.5 h at 25°C). The purple corn cob extract obtained by isostatic processing at 650 MPa and 65 °C presented high antioxidant activity and content of bioactive compounds, unlike the conventional extraction of 2.5 h and 65 °C (p < 0.05). However, it did not show a significant difference with the extract obtained at 450 MPa and 45 °C (p > 0.05). Seven different anthocyanins were identified by liquid chromatography in the extracts obtained by high isostatic pressure (650 MPa at 65 °C) and hydroalcoholic maceration (2.5 h at 65 °C), mainly cyanidin-3-glucoside, pelargonidin-3-glucoside and peonidin-3-glucoside, and their respective malonyl derivatives. The high isostatic pressure increased the extraction of bioactive compounds by more than 50% and obtained them in shorter times, thus appearing as a new alternative, and eco-friendly method for the extraction of bioactive compounds from plant tissues.